Study on Volatile Compounds of Gelatine and The Maillard Reaction Products from Different Species Using SPME-GCMS - Ismarti Ismarti; Dody Dwi Handoko; Kuwat Triyana; Hamzah M. Salleh; Nurrulhidayah A. Fadzillah; Noor Faizul Hadry Nordin (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Food fraud and adulteration are the global issues, currently. One important issue is about gelatine since it comes from many sources of animals. Therefore, analytical method for gelatine must be developed and used for the authentication. This study was conducted to investigate the Volatile Compounds (VCs) of gelatine and the Maillard Reaction Products (MRPs) which are responsible to their aroma. Three gelatine standards from bovine, fish and porcine bought from Sigma Aldrich were used. A high reactivity reducing sugar namely xylose was used in the Maillard Reaction (MR). A Solid Phase Micro Extraction-Gas Chromatography-Mass Spectroscopy (SPME-GC-MS) used to evaluate the VCs in the samples. The VCs were identified by comparing the mass spectra of the compounds with database of NIST library. Moreover, retention time using the n-Alkane index were compared with literature data. There were 67 VCs have been identified. Among them, furfural, acetic acid, nonanone, dimethyl disulphide and decanone were considered as the important volatiles in gelatine due to its abundance. In the MRPs, furfural, 1-(2-furanylmethyl)-1H-pyrrole, 1-(2-furanyl)- ethanone, acetic acid and 2,2’-bifuran were predominant. Additionally, heptanol, octanal, nonanal, nonanone, dimethyl disulphide and dimethyl trisulphide could be considered as the important compounds due to its low odour threshold value. The compounds had a direct influence on the overall aroma of samples and could be potential to use in gelatine differentiation.